The Position of Adopted Children (Mangain) in Obtaining the Status of the Heirther According to the Batak Toba Traditional Instruction Law - Ning Adiasih (Eduvest - Journal of Universal Studies, 2022)
The adoption of adopted children in the Toba Batak community is carried out in an open and cash way. The main reason in the Toba Batak community is the absence of descendants. The indigenous Batak Toba community itself adheres to a patrilineal system that is based on male/father lineage. The requirements for adopting children by the Toba Batak indigenous people are carried out according to the customs of the indigenous people, by carrying out a traditional ceremony "dirajahon" in front of dalihan na tolu, traditional leaders / leaders, and local indigenous people by giving ulos parompa (carpet) and dekke sitio. tio (carp) as evidence of an inauguration in the process of the traditional ceremony. The position of an adopted child is basically legal to become an heir and his rights are equal to the position of a biological child, because according to the customary inheritance law of the Toba Batak with evidence of the existence of the traditional ceremony, an adopted child is legally the heir of his adoptive parents himself, without the need for tools. evidence as well as a deed. Adopted children have the right to joint property and inheritance from their adoptive parents